Effect and mechanism of Kangfuxin liquid on oral ulcer in patients with chemotherapy treated hematologic malignancies: Network pharmacology study and clinical observations. (2021) - Bo, Linyu; Zhang, Yulin; Wu, Xiumei; Ma, Ancui; Zhao, Yu; Liu, Heng; He, Miao; Zhang, Chenggui
Abstract: Background: Oral ulcer (OU) is a common oral mucosal disease, which has a high prevalence in patients with malignant tumors, leading to systemic infection which can be life-threatening. Kangfuxin liquid (KFX), as a traditional Chinese medicine, has been widely used in the treatment of ulcers and dermatologic lesions in recent years, and has shown effective results. However, there are few descriptions of its efficacy in the treatment of oral ulcer caused by chemotherapy in patients with hematological malignancies, and its mechanism of action is not clear. Method: Retrospective clinical study and network pharmacology-based method were utilized in this study. First of all, we collect clinical research data by using the hospital's historical electronic medical records, and later it was analyzed to describe its clinical efficacy. Secondly, the effective components and the inferred targets of KFX were obtained by the collected literatures and SwissTargetPrediction database. Then, an interaction network between shared targets of KFX and OU was constructed using STRING online tool. Topological analyses were performed to extract hub gene targets. The gene target pathway of KFX was analyzed by David database. Finally, molecular docking was used to predict the binding mode and affinity. Results: Clinical observation showed, KFX can effectively shorten the healing duration of ulcer and time for pain relief, limit the occurrence and development of oral diseases, and improve the quality of life of patients. In addition, in the past six years, no adverse drug reactions were recorded. Network pharmacological analysis data show that PI3K-Akt signaling pathway, RAP1 signaling pathway and TNF signaling pathway together plays an important role in the treatment of oral ulcer with KFX. Through molecular docking technology, we also believe that AKT1 and MMP9 are the core potential targets of KFX in the treatment of OU. Conclusions: Application of network pharmacology and molecular docking provides new insights on the efficacy, active ingredients and molecular mechanism of KFX in the treatment of oral ulcer, and preliminarily reveals the pharmacological mechanism of KFX in the treatment of OU through the characteristics of "multi-components, multi-targets, and multi-approaches" synergistic effect. Graphical abstract: Image 1 Highlights: KFX can effectively shorten the healing duration of ulcer and time for pain relief, and improve patients' quality of life. The signaling pathways, PI3K-Akt, RAP1, TNF, together plays an important role in the treatment of oral ulcer with KFX. AKT1 and MMP9 are the core potential targets of KFX in the treatment of Oral ulcers.